A Note on Nominal and Real Devaluation in Laos. (April 2015) - Kyophilavong, Phouphet; Shahbaz, Muhammad; Uddin, Gazi Salah
In this article, we investigate whether or not nominal devaluation leads to real devaluation in Laos by using autoregressive-distributed lag (ARDL) bounds testing and the Granger causality test in a vector error correction model (VECM) framework. Our empirical evidence shows that nominal devaluation Granger causes real devaluation in the short run and the long run. This finding implies that nominal devaluation leads to real devaluation.